Ethnobotanical Study and Conservation of Medicinal Plants Among Communities in Blang Pegayon, Gayo Lues Regency - Maryam, Asni; Djufri, Djufri; Andayani, Dewi; Wardiah, Wardiah; Ruselli Puspa, Vivera; Arief Pratama, Ucha (Universitas Islam Negeri Ar-Raniry, 2025)
Blang Pegayon Subdistrict, Gayo Lues Regency, is one of the regions with high biodiversity and is renowned for its role in traditional medicine. This study aimed to identify the medicinal plant species used by local communities, the plant parts utilized, processing methods, and conservation strategies applied. The research population consisted of residents of Blang Pegayon Subdistrict, Gayo Lues Regency, with purposive sampling involving 48 respondents from six villages based on the presence of traditional medicinal plant use, including both key and non-key informants. Data were collected through semi-structured interviews, observation, plant identification using the Picture This application and the Plants of the World Online (POWO) database, and documentation. The data were analyzed descriptively. The findings revealed 51 medicinal plant species belonging to 29 families. The leaf was the most frequently used plant part (58%), while the most common processing method was pounding (26%). Conservation efforts were carried out through cultivation in home gardens (40%), planting in fields or farms (40%), and the use of wild plants from surrounding environments (20%). The results of this study are expected to provide valuable information for the development of future sustainable research. Keyword: etnobotany; conservation; traditional; medicine plant.